2019
DOI: 10.1093/neuonc/noz175.998
|View full text |Cite
|
Sign up to set email alerts
|

Stem-25. Hdac1 Is Essential for Glioma Stem Cell Survival

Abstract: OLIG2 is a central nervous system-specific transcription factor that is expressed in almost all diffuse gliomas. It is also one of the key core transcription factors that can reprogram differentiated glioma cells to highly tumorigenic glioma stem-like cells (GSCs). We have previously shown that expression of OLIG2 is critical for glioma growth both in a genetically relevant mouse model as well as in patient-derived xenograft models. Our work suggests that a small molecule inhibitor of OLIG2 could serve as a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…HDAC1 ablation significantly decreased stemness and proliferation in patient-derived GSCs in a p53-dependent manner. By contrast, it had only minimal impact on normal human neural stem cells and astrocytes ( Lo Cascio et al, 2019 ). HDAC1 knockdown inhibited the epithelial–mesenchymal transition transcription factors TWIST1 and SNAIL, downregulated the mesenchymal marker matrix metalloprotein-9, and upregulated the epithelial marker E-cadherin 34.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HDAC1 ablation significantly decreased stemness and proliferation in patient-derived GSCs in a p53-dependent manner. By contrast, it had only minimal impact on normal human neural stem cells and astrocytes ( Lo Cascio et al, 2019 ). HDAC1 knockdown inhibited the epithelial–mesenchymal transition transcription factors TWIST1 and SNAIL, downregulated the mesenchymal marker matrix metalloprotein-9, and upregulated the epithelial marker E-cadherin 34.…”
Section: Discussionmentioning
confidence: 99%
“…GO enrichment and KEGG pathway were analyzed with OmicShare Tools. Previous studies have evaluated the roles of certain HDAC family members in glioma (Lodrini et al, 2013;Wang et al, 2017;Lo Cascio et al, 2019;Song et al, 2020). A previous study has indicated that the NFAT2-HDAC1 pathway may maintain the malignant phenotype and promote mesenchymal transition in glioma stem-like cells (GSCs).…”
Section: Discussionmentioning
confidence: 99%